A new species of Acestrocephalus (Characiformes: Characidae) from Venezuela - Lasso, Carlos A (2000)
A new species of Acestrocephalus is described from 60 specimens collected in the Río Orinoco and Río Negro drainages, Venezuela. This species is distinguished. from aH other Acestrocephalus by the combination of the foHowing characters: anal rays, 29-36; 63-71 perforated scales on (he lateral line; 10-12 scales aboye and 9-12 below the lateral line; 39-52 teeth on the maxil!ary; 9-12 premaxillary teeth; 8-12 teeth in the inner row on the dentary; 5-7 gil! rakers on the lower part of (he first gil! arch; humeral, peduncular and caudal blotch absent